PENINGKATAN KEAKTIFAN DAN PRESTASI BELAJAR MATEMATIKA MELALUI MODEL COOPERATIVE LEARNING TIPE TGT (TEAMS GAMES TOURNAMENT) PADA SISWA KELAS V - Wikan Budiarti (Universitas Sarjanawiyata Tamansiswa, 2014)
The purposes of this research were to improve the activity and learning outcomes in mathematics of students 5th grade Balingasal 1 Public Elementary School through cooperative learning type Teams Games Tournament. The subjects of this research is 29 students of 5th grade Balingasal 1 Public Elementary. The object of this research were student’s activity and mathematics learning outcomes. The result showed that after treatment with cooperative learning type Teams Games Tournament at 5th grade Balingasal 1 Public Elementary School, activity and mathematics learning outcomes of students has increased. This was indicated by an increasing in the result percentage average activity of 36,64% in the pre-action, whereas at the first cycle improves with average percentage to 59,41%, improves in the second cycle to 77,16%. Mathematics learning outcomes of students also increased. The average of students learning outcomes in pre-action is 49,81. In the first cycle, the average result improves to 63,97. In the second cycle, the average result improves to 75,88. In conclusion, cooperative learning type Teams Games Tournament can improve activity and mathematics learning outcomes.